(3GdNUGFUs - (3YKeGf Hf Lfj GdehUdj, CHh GdaJM, GHf Lfj,J (B392 (3g` s ((3eMeO Hf ejcGFjd s)
(3ChdgG (B:s
(3GdMeO ddg GdhGMO GdYOd GdbOje gPG CWGd Gddg HbGA ehdGfG GdSjO GdefUhQ cJGH de CRd Ydi aGQW GdMGd s
(3BNQgG (B:s
(3ef HGH ai NdY GdCOdI , bhdg (B: (3cPdc bhdg GdYLGL (B: (3hbO cQQ Pdc Cdh Ydi QMeg Gddg ai ZjQ ehVY aZfjfG Yf EYGOJg s
(3HChdgG agQS ddCHhGHs
(3ai GddZIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B204 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B251 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B652s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GddZIs